Landslide hazard assessment and their application in land management in Kendari, Southeast Sulawesi Province, Indonesia - La Ode Restele; Ahmad Hidayat; Fitra Saleh; L M Iradat Salihin (Journal of Degraded and Mining Lands Management, 2023)
Kendari is the capital of Southeast Sulawesi Province which is prone to landslides. Good land management needs to be done to minimize the impact of landslides. This study aimed to map the Kendari landslide hazard that can be used as an input into land management strategy, especially in vulnerable to the threat of landslides. The primary data used in this study were DEMNAS and Sentinel-2. Landslide detection was carried out using a Process Hierarchy Analysis (AHP) approach and validated by field surveys. Land capability analysis was based on landform analysis using land system data. Land management directions were carried out based on the integration of landslide hazard analysis with the ability of the land to be calibrated with actual land cover. The analysis showed that areas with high and very high landslide hazards reached 2654.09 ha (9.64%) and 4354.78 ha (15.82%). Capability class of VII is spread over structural hills to the north and south of Kendari with an area of 7,215.81 ha (26.21%). Land management in areas with very high landslide hazards and land capability class VII is to add cover crops on land that is not protected by a canopy. Cover crops that can be added are the grass type to minimize the danger of erosion that can trigger landslides.